THE IMPACT OF DAYLIGHT APERTURES AND REFLECTIVE SURFACES ON THE EFFECTIVENESS OF NATURAL LIGHTING AT THE RUMAH KINDAH OFFICE IN JAKARTA - Panjaitan (Jurnal Riset Arsitektur, 2018)
Abstract - Illumination forms an important factor in a building. Lighting, and especially its natural form, is an important element to be considered in an office building. Proper natural lighting in an office can create a way to economize on energy. Besides, it may create a conducive atmosphere, affecting the work spirit and inspire the zest of the employees, so a lighting system must be designed to reach the highest possible degree of effectiveness. The effectiveness of natural lighting can be regarded from the quantitative and qualitative angle. Attaining the purpose of naturadaylight is influenced by various factors, including the daylight apertures that let daylight or sunlight seep in, along with surfaces or panels that reflect light so that it bounces back. Therefore, we must find out how these daylight apertures and reflective surfaces influence the effectiveness of lighting in office buildings. The Rumah Kindah office in Jakarta happens to be one of the office buildings that make use of natural lighting with daylight apertures that are unique, along with several kinds of reflective surfaces. This type of research can be classified as descriptive-evaluative, making use of the quantitative-qualitative approach. The Rumah Kindah office as the object of rsearch consists of three work spaces displaying the characteristics of daylight apertures that are uniform but not exactly the same, and the same applies to the reflective surfaces, so the research was conducted in these three office rooms. The relevant set of data was collected by way of observation, taking measurements and through the medium of interviews held at the object of research as well as using software to support simulation for the sake of acquiring the data required. These data can be analyzed by employing the theories that are available. The analysis results indicate that the daylight apertures oriented to the East-West but differing in terms of type, position, dimension and material produce a quantity and quality that varies from space to space. Besides, the reflective surfaces inside and outside the rooms play an important role in attaining the desired effectiveness of natural lighting in each of the work spaces at the Rumah Kindah office in Jakarta. Keywords : Light Apertures, Reflective Surfaces, Effectiveness of Natural Lighting